Perbandingan Ruang Warna RGB dan HSV dalam Klasifikasi Kematangan Biji Kopi - Haidar Azmi Rabbani; Muh. Arif Rahman; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Coffee is one of the most popular drinks in the world, and is favored by many group, including in Indonesia. The taste image of coffee has the characteristics of each type of coffee. One thing that influences the image of the taste of coffee is the maturity of the coffee beans. For this reason, an introduction to the level of maturity of coffee beans is carried out by utilizing the color space of the coffee bean image. The research conducted utilizes a comparison of the extraction of RGB and HSV color spaces as the first test and the addition of LBP texture extraction in the second test. Based on tests carried out on 500 images of coffee beans, the best accuracy was 99.2% in the first test and 98.2% in the second test. Testing using a backpropagation neural network.